The shame of one million deaths - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
More than one million people die each year through work-related accidents and sicknesses in the agricultural sector, according to new statistics from the International Labour Organisation (ILO). Previous figures said that more than half of the...